TENUN TRADISIONAL SEBAGAI UPAYA PELESTARIAN SUMBER EKONOMI LOKAL DI DESA HUTA RAJA KAMPUNG ULOS - Abdi Tanjung; Marajudan Rambe; Listiya Dasopang; Suriyanti Suriyanti; Ledis Ratna Sari Simbolon (Lembaga Pengembangan Kinerja Dosen, 2024)
Ulos cloth has long been used by the Batak people and has become a cultural heritage. Ulos cloth is used in various gatherings and also traditional events such as weddings, funerals, seven months or events within the family circle. Current developments have made ulos cloth endangered because the economic conditions of ulos craftsmen are not developing, so they do not want to continue their profession as craftsmen. Ulos Village, Lumban Suhi Suhi Toruan Village, Samosir Island, where the majority of the people work as weavers, so the village is called ulos village. The people there sell their ulos through bazaars, exhibitions, and to visiting tourists. Pondok Raja ulos village carries out empowerment to develop ulos cloth in order to preserve the revitalization and utilization of available natural resources, including developing the village as a tourist village. This research uses the theory of participatory communication and community empowerment. The data collection technique is by conducting interviews with the management or craftsmen of the ulos. This research also carried out on-site observations by looking at how community empowerment with ulos craftsmen has improved the MSMEs of North Sumatra, especially in Lake Toba.